PLGA-based drug delivery systems in treating bone tumors - Qiu, Enduo; Liu, Fei (Frontiers in Bioengineering and Biotechnology, 2023)
The bone tumor has become a common disease that endangers human health. Surgical resection of bone tumors not only causes biomechanical defects of bone but also destroys the continuity and integrity of bone and cannot altogether remove the local tumor cells. The remaining tumor cells in the lesion bring a hidden danger of local recurrence. In order to improve the chemotherapeutic effect and effectively clear tumor cells, traditional systemic chemotherapy often requires higher doses, and high doses of chemotherapeutic drugs inevitably cause a series of systemic toxic side effects, which are often intolerable to patients. PLGA-based drug delivery systems, such as nano delivery systems and scaffold-based local delivery systems, can help eliminate tumors and promote bone regeneration and therefore have more significant potential for application in bone tumor treatment. In this review, we summarize the research progress of PLGA nano drug delivery systems and PLGA scaffold-based local delivery systems in bone tumor treatment applications, expecting to provide a theoretical basis for developing novel bone tumor treatment strategies.